PORTRAYAL OF GENDER DISCRIMINATION: A STUDY OF THREE INDIAN ENGLISH CRITIC WOMEN PLAYWRIGHTS - Surinder Singh, Dr.Richa Sharma, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
India has been a land of articulate feelings, eloquent speeches and diverse cultural manifestations; Indian drama comprises all the three. India‘s tradition of drama goes back to Bhasa, the Sanskrit dramatist (fifth century B.C.E.), continuing through Kalidasa and Bhavabhuti. The Natyashastra by Bharata Muni is the oldest text on dramaturgy in the world. However, Indian English drama has always lagged behind poetry and fiction. As K.R. Srinivasa Iyengar pointed out in 1962: Modern Indian dramatic writing in English is neither rich in quantity nor, on the whole, of high quality. Enterprising Indians have for nearly a century occasionally attempted drama in English, but seldom for actual stage production. (Iyengar, 226)